2016
DOI: 10.1108/gm-04-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Doing masculinities in construction project management

Abstract: Purpose This study aims to examine how masculinities are (re)produced in project-based organizations. The authors first investigate the doing of masculinities in everyday work practices in construction project management. Second, the authors investigate whether there are opportunities to perceive, or do, gender differently in this specific context. Design/methodology/approach Data are elicited from a case study of construction project managers working on a infrastructure project. The project managers were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
(143 reference statements)
1
10
0
Order By: Relevance
“…This is similar to previous research that demonstrates that employees in construction are expected to tolerate adverse work conditions, with help-seeking behaviours discouraged (Stergiou-Kita et al, 2015). It is also consistent with Olofsdotter and Randevåg (2016) who found that norms of masculinity Work, Employment and Society 2021, Online First Author post peer-review version Original article available at: https://doi.org/10.1177/0950017020978914 in the construction industry result in both men and women adjusting their working styles to 'fit in'. Subtle differences were also identified in the effects of the gendered rules for men and women's wellbeing.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to previous research that demonstrates that employees in construction are expected to tolerate adverse work conditions, with help-seeking behaviours discouraged (Stergiou-Kita et al, 2015). It is also consistent with Olofsdotter and Randevåg (2016) who found that norms of masculinity Work, Employment and Society 2021, Online First Author post peer-review version Original article available at: https://doi.org/10.1177/0950017020978914 in the construction industry result in both men and women adjusting their working styles to 'fit in'. Subtle differences were also identified in the effects of the gendered rules for men and women's wellbeing.…”
Section: Discussionsupporting
confidence: 90%
“…A centre-margin structure is in play where hegemonic masculinity becomes the centre and the subordinate masculinity is at the margin of the discourse (Bruni and Perrotta, 2014; Verduijn and Essers, 2013). On this scale, various masculinities exist and they are affected by each other’s development (Giazitzoglu and Down, 2017; Olofsdotter and Randevåg, 2016). These multiple masculinities are negotiated through competing tensions between hegemonic and subordinate masculinities (Boyle, 2002; Olofsdotter and Randevåg, 2016; Fisher and Kinsey, 2014).…”
Section: Theoretical Framework – the Masculine Entrepreneurmentioning
confidence: 99%
“…Moreover, the majority of women working in construction perform administrative work (Rodríguez-Garzón et al , 2015; Simon, 2013; Ness and Green, 2012), while those controlling “technical”, “fee-earning” careers are mostly men (Galea et al , 2015). Even in the Swedish labor market, described as a gender-equality champion, female project managers are mainly found at headquarters or in softer areas such as landscaping and planning, or special posts related to the environment or quality (Olofsdotter and Randevåg, 2016; Olofsdotter and Rasmusson, 2016; Arditi et al , 2013).…”
Section: Introductionmentioning
confidence: 99%